2022
DOI: 10.1007/s42773-022-00161-2
|View full text |Cite
|
Sign up to set email alerts
|

Insights into simultaneous adsorption and oxidation of antimonite [Sb(III)] by crawfish shell-derived biochar: spectroscopic investigation and theoretical calculations

Abstract: Removal of antimonite [Sb(III)] from the aquatic environment and reducing its biotoxicity is urgently needed to safeguard environmental and human health. Herein, crawfish shell-derived biochars (CSB), pyrolyzed at 350, 500, and 650°C, were used to remediate Sb(III) in aqueous solutions. The adsorption data best fitted to the pseudo-second-order kinetic and Langmuir isotherm models. Biochar produced at 350°C (CSB350) showed the highest adsorption capacity (27.7 mg g− 1), and the maximum 78% oxidative conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 68 publications
(109 reference statements)
1
2
0
Order By: Relevance
“…SAWC was pyrolyzed at 900 °C, wherein the thermal reorganisation of organic structures lowers the PFR content, 65 making quinoid moieties the likely driver for Sb(III) oxidation. [66][67][68] These results corroborate findings by Zhong et al 69,70 who demonstrated that electron accepting moieties i.e., PFR and quinoid groups in rice husk biochar were able to oxidise As(III) to As(V). Therefore, BC induced oxidation of metal(loid)s such as Sb(III) can limit their sorption by BC.…”
Section: Oxidation To Sb(v) Limits Sb(iii) Removal By Sawcsupporting
confidence: 87%
“…SAWC was pyrolyzed at 900 °C, wherein the thermal reorganisation of organic structures lowers the PFR content, 65 making quinoid moieties the likely driver for Sb(III) oxidation. [66][67][68] These results corroborate findings by Zhong et al 69,70 who demonstrated that electron accepting moieties i.e., PFR and quinoid groups in rice husk biochar were able to oxidise As(III) to As(V). Therefore, BC induced oxidation of metal(loid)s such as Sb(III) can limit their sorption by BC.…”
Section: Oxidation To Sb(v) Limits Sb(iii) Removal By Sawcsupporting
confidence: 87%
“…The peaks of C 1 s (Fig. 1 c) with the binding energy of 284.78 eV and 284.78 eV related to the structure of C=C and C=O/C–O 31 , 32 . These results could be contributed to the generation of oxygen-contained functional groups during pyrolysis processes.…”
Section: Resultsmentioning
confidence: 98%
“…We accurately calculated that vdW, π–π bonds and H-bonds between the biochar and PHA were the dominant bonds, and a biochar molecule could absorb four molecules of PHA. The results are found in pollutant adsorption on biochar [ 46 , 47 ]. DFT, IGM and molecular dynamics were the first to be used to study autotoxin adsorption on biochar.…”
Section: Discussionmentioning
confidence: 99%